Credit and Prices in Woodford’s New Neoclassical Synthesis (2015)
ABSTRACT: Following recent debates on the New Neoclassical Synthesis, the theory of monetary policy has been renewed. The prevailing method, illustrated by Woodford’s version of Interest and Prices, is a Dynamic Stochastic General Equilibrium Model in which the old LM curve is voluntarily substituted by an optimal monetary rule. Such a turning point requires a peculiar set of assumptions, especially regarding monetary prices. The recent debate pays attention to de-emphasis on the nominal monetary aggregate, which does not play any explicit role in monetary policy deliberations. Following Calvo’s model, Woodford’s neo-Wicksellian framework only considered monetary prices in equilibrium. This article demonstrates that even though the New Neoclassical Synthesis considers it essential to have a monetary theory for policymaking, the former offers the same answers as the traditional static macroeconomics. More precisely, it shows that the use of dynamic optimisation – such as the one developed by Woodford’s approach – does not contribute in a decisive way to improving our understanding of the role that money prices play in monetary theory. Woodford’s canvas is silent about the mechanisms whereby monetary policy induces agents to adjust individual money prices to the values that generate an equilibrium price level. Thus, if we want to close this gap, it may be useful to consider a ‘forward guidance’ strategy. By means of such a tool, central bankers are able to shape the public’s expectations on economic outcomes by pre-announcing the time path of future policy actions.